Albania : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1997)
This paper describes economic developments in Albania during the 1990s. Macroeconomic performance deteriorated in 1996, as the fiscal stance was weakened ahead of the parliamentary elections in May. Although two large public sector wage increases contributed, it was mainly revenue shortfalls that drove the domestically financed budget deficit to more than 10 1\2 percent of GDP-the highest level since 1992. Reflecting higher demand in the economy, the trade deficit increased from 19 1\2 percent of GDP to 25 percent of GDP, and inflation nearly tripled to 17 1\2 percent.